Phosphate-solubilizing rhizobacteria from wild sorghum enhance growth of cultivated sorghum under rock phosphate fertilization - Benson Ouma Nyongesa; Becky Nancy Aloo; Beatrice Ang’iyo Were (Discover Sustainability)
Abstract Phosphorus (P) deficiency is a major constraint to crop production. Phosphate-solubilizing bacteria (PSB) offers a sustainable alternative to synthetic fertilizer application. However, the identity, efficiency, and growth-promoting potential of PSB in the rhizosphere of wild sorghum (Sorghum halepense L. Pers) remain poorly understood. This study aimed to determine the genetic diversity of rhizobacteria associated with wild sorghum, assess their ability to solubilize various insoluble phosphate sources and evaluate the potential of broad-spectrum PSB to enhance the growth of cultivated sorghum (Sorghum bicolor L. Moench) under Mijingu rock phosphate (MRP) fertilization. Rhizobacteria were characterized based on morphological, biochemical, and genetic traits. The ability to solubilize calcium phosphate, aluminum phosphate, inositol phosphate, and MRP was tested using the National Botanical Research Institute Phosphate medium. A greenhouse study was conducted to evaluate the growth-promoting potential of broad-spectrum PSB, including Citrobacter sp. SB02-1 and SB04-3, Serratia sp. SB03-1, and Raoultella sp. SB07-2, in MRP-fertilized sand. Sixteen bacterial isolates were identified, representing species such as Proteus sp., Pseudomonas sp., Raoultella sp., Citrobacter sp., Morganella sp., Serratia sp., Enterobacter sp., and Klebsiella sp. These isolates exhibited diverse abilities to solubilize insoluble phosphate sources, with Citrobacter sp. SB02-1 and Citrobacter sp. SB04-3 releasing the highest quantities of P (> 100 mg/l). Inoculation with Citrobacter sp. SB04-3 significantly improved sorghum growth, resulting in increases in the number of leaves (66.7%), shoot length (61.3%), root length (89.3%), root biomass (212.5%), and dry weight (280%) compared to non-inoculated plants. Remarkably, the performance of Citrobacter sp. SB04-3 was comparable to plants treated with balanced soluble fertilizers without inoculation. This study is among the first to demonstrate that Citrobacter sp. SB04-3, isolated from wild sorghum rhizosphere, can match the performance of synthetic fertilizers by significantly enhancing sorghum growth and biomass under MRP fertilization. This novel finding highlights its potential as a cost-effective and sustainable alternative for P management in agriculture.